2018
DOI: 10.1016/j.pedneo.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Atropine use may lead to post-operative respiratory acidosis in neonates receiving ductal ligation: A retrospective cohort study

Abstract: The use of atropine as premedication in general anesthesia for neonatal PDA ligation is associated with higher risk of respiratory acidosis, which worsens with the combined use of ketamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Early experimental and clinical studies have reported that structurally-related tropane alkaloids (such as anisodamine, scopolamine, and atropine) have potential undesirable effects on the cardiovascular and respiratory systems. [13][14][15][16][17][18] Thus, it is necessary to investigate the effects of Ani on cardiorespiratory function systematically. Additionally, although some drugs, such as antibiotics, tricyclic antidepressants, and antifungal agents do not act on the cardiovascular system directly based on their mechanism of action, nonetheless they have been reported to lead to life-threatening adverse effects, and some patients have suffered serious heart damage after taking these drugs in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Early experimental and clinical studies have reported that structurally-related tropane alkaloids (such as anisodamine, scopolamine, and atropine) have potential undesirable effects on the cardiovascular and respiratory systems. [13][14][15][16][17][18] Thus, it is necessary to investigate the effects of Ani on cardiorespiratory function systematically. Additionally, although some drugs, such as antibiotics, tricyclic antidepressants, and antifungal agents do not act on the cardiovascular system directly based on their mechanism of action, nonetheless they have been reported to lead to life-threatening adverse effects, and some patients have suffered serious heart damage after taking these drugs in clinical practice.…”
Section: Introductionmentioning
confidence: 99%